Host delivered-RNAi of effector genes for imparting resistance against root-knot and cyst nematodes in plants. (April 2022) - Joshi, Ila; Kohli, Deshika; Pal, Akansha; Chaudhury, Ashok; Sirohi, Anil; Jain, Pradeep K.
Abstract: Plant-parasitic nematodes (PPNs) are a major threat to crop production worldwide, with root-knot nematodes ( Meloidogyne spp.) and cyst nematodes ( Globodera spp.) being the most devastating and widespread. They induce drastic changes in plant cells, leading to the development of specialized feeding cells essential for nematode growth, development and reproduction. PPNs secrete certain effector proteins from their esophageal glands which play crucial role in establishing the host-parasite relationship and are involved in both early and later stages of nematode parasitism. The conventional strategies for controlling these harmful nematodes have several limitations including environmental issues associated with the use of nematicides and only few natural resistance genes against PPNs in different crops. Of late, RNA interference (RNAi) has emerged as one of the most promising strategy for managing PPNs. The host-mediated RNAi approach, targeting nematode genes, involves both plants and nematode RNAi machinery and is the most promising approach for development of nematode resistance in plants. So far, the suppression of effector or secretory class of proteins has resulted in highest rate of reduction in nematode infection, thereby making this class of genes as the most effective targets for RNAi based strategy. In this review we highlight the success stories of host-mediated RNAi approach by use of effector proteins, as the most favorable targets, for development of resistance against root-knot nematodes and cyst nematodes. Highlights: This review is a comprehensive collection of the research work on HD-RNAi of plant parasitic nematode effector genes. The review open avenues for imparting resistance in crop plants via gene silencing. Further it helps in understanding the detailed RNAi pathway and its manipulation to manage the menace by pathogens in detail.